Identification of Lupus Podocytopathy with Coexistent Glomerular Diseases – A Case Report. (28th October 2020) - Ding, L; Tomaszewski, J; Liu, L; Murray, B
Abstract: Introduction/Objective: Lupus podocytopathy (LP), featured by nephrotic syndrome, is a unique subtype of lupus nephritis that mimics minimal change disease or primary focal segmental glomerulosclerosis (FSGS) on renal biopsy with diffuse podocyte foot process effacement and no capillary-loop immune deposits. LP usually presents on a background of ISN/RPS class I or class II lupus nephritis, and very rarely may present without immune deposits. Diagnosis of LP, when confounded by other glomerular diseases associated with nephrotic syndrome, can be very challenging and requires thorough clinical and pathology correlations. Methods: Here we report a case of LP in a patient with nephrotic syndrome and multiple comorbidities affecting kidneys. A 24-year-old female with type-I diabetes, psoriasis, and intermittent arthritis/rash of unknown etiology, presented with abrupt onset of nephrotic proteinuria attributed to recent low dose prednisone therapy, and renal insufficiency. A renal biopsy showed nodular glomerulosclerosis and FSGS. No immune deposits were identified by immunofluorescence or electron microscopy. Ultrastructurally there was also diffuse glomerular basement membrane thickening and over 90% podocyte foot process effacement. With no established systemic lupus erythematosus (SLE), the case was initially diagnosed as diabetic nephropathy with coexistent FSGS as the etiologies for nephrotic proteinuria, and the patient was put on ACEI and diuretics. However, massive proteinuria persisted, and the patient also developed pancytopenia. Serology concurrent with the biopsy came out later showing positive autoantibodies against dsDNA, Smith, and Histone. With continued worsening of creatinine, a renal biopsy was repeated revealing essentially similar findings to the first biopsy. Results: Integrating the serology results and clinical presentation, SLE was favored. The pathology findings were re- evaluated and considered to be most consistent with LP and coexistent diabetic nephropathy, with FSGS either a component of LP or an independent lesion secondary to diabetes or hypertension. The patient was started with high dose prednisone at 60 mg/day. One month later, her proteinuria, serum creatinine, pancytopenia, skin rash, and arthritis were all significantly improved. Conclusion: LP can be easily masked by coexistent glomerular diseases. Sufficient awareness of the entity is necessary for the appropriate diagnosis and treatment.